1985
DOI: 10.1590/1809-43921985152018
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de cupinzeiro e esterco de galinha como adubo em alface num Podzólico Vermelho Amarelo da região de Manaus

Abstract: O pequeno agricultor de terra firme da Amazônia tem dificuldades em produzir hortaliças para seu próprio consumo ou para comercialização uma vez que os solos locais são de baixa fertilidade e os preços dos adubos minerais são elevados. Com o objetivo de proporcionar novas alternativas para estes agricultores, foi realizado um experimento de campo com alface num Podzólico Vermelho Amarelo da região de Manaus. Utilizaram-se esterco de galinha, adubação química básica (N,P,K) e cupinzeiro (gênero Nasutiermes, o m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
6
1
1
Order By: Relevance
“…The high aluminium content in the nests may be due to the fact that a good part of the nest material originated from inundation forests on clayey soil (várzea). Some of the data presented in OLIVEIRA & PAIVA (1985) for the same site are quite different (TABLE 1b), probably because the soil quality on this intensively used experimental plot is rapidly changing. Nest material of wood-feeding Nasutitermes (TABLE la) had the same high carbon content as wood (MARTIUS, 1989), whereas the C in soil-feeder nests was lower (TABLE 1b).…”
Section: Comparison Of Soil and Nest Material: Table 1amentioning
confidence: 98%
See 1 more Smart Citation
“…The high aluminium content in the nests may be due to the fact that a good part of the nest material originated from inundation forests on clayey soil (várzea). Some of the data presented in OLIVEIRA & PAIVA (1985) for the same site are quite different (TABLE 1b), probably because the soil quality on this intensively used experimental plot is rapidly changing. Nest material of wood-feeding Nasutitermes (TABLE la) had the same high carbon content as wood (MARTIUS, 1989), whereas the C in soil-feeder nests was lower (TABLE 1b).…”
Section: Comparison Of Soil and Nest Material: Table 1amentioning
confidence: 98%
“…Recently, the positive reaction of plant growth to treatment with organic material derived from termite nests has been demonstrated in natural and agricultural systems (OKELLO-OLOYA & SPAIN, 1986;RAJAGOPAL, et al 1990, SPAIN & OKELLO-OLOYA, 1985. Under Amazonian conditions, the growth of lettuce can be enhanced by enrichment of the soil with termite nest material (OLIVEIRA & PAIVA, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…A significant effect of the mound material in the development of lettuce and passion fruit seedlings was verified by Oliveira and Paiva (1985) and Souza et al (2011), respectively.…”
Section: Resultsmentioning
confidence: 85%
“…2c). Oliveira and Paiva (1985) evaluating the production of lettuce, found that the application of 50 g of termite mound material (whole crushed mound) increased in 288% the shoot mass of this crop, compared to the control. Novelino et al (2011) verified that the dose of 76.2 g of termite mound material increased in 62% the shoot dry mass production of sorghum.…”
Section: Effect Of the Substrate On Early Seedling Growthmentioning
confidence: 97%
See 1 more Smart Citation